2020
DOI: 10.1002/cbf.3491
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of long non‐coding RNAs in the synovial membrane of osteoarthritis patients

Abstract: Osteoarthritis (OA), the most common chronic joint disease in the elderly, has become a significant economic burden for families and societies worldwide. Although treatments are continually improving, current drugs only target joint pain, with no effective therapies modifying OA progression. Long noncoding RNAs (lncRNAs), which have received increasing attention in recent years, are abnormally expressed in OA cartilage. In the present study, weighted coexpression network analysis (WGCNA) was applied to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…It has been reported that some risk pathways such as TGF-β signaling pathway and inflammatory bowel disease and risk biological processes such as chondrocyte differentiation and regulation of cartilage development are involved in the OA pathology [ 56 ]. Functional analysis of lncRNA in the synovial membrane of osteoarthritis patients revealed that lipopolysaccharide, angiogenesis, tumor necrosis factor (TNF) signaling, and mitogen-activated protein kinase (MAPK) signaling pathways might contribute to OA development [ 57 ]. Interestingly, our GO and KEGG analysis showed that several unreported processes such as muscle cell proliferation, cell-cell adhesion, and chemokine ligand 2 production and signaling pathways including Hippo signaling pathway, Wnt signaling pathway, and Ras signaling pathway were particularly identified in Tibetan OA patients compared to the Chinese Han OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some risk pathways such as TGF-β signaling pathway and inflammatory bowel disease and risk biological processes such as chondrocyte differentiation and regulation of cartilage development are involved in the OA pathology [ 56 ]. Functional analysis of lncRNA in the synovial membrane of osteoarthritis patients revealed that lipopolysaccharide, angiogenesis, tumor necrosis factor (TNF) signaling, and mitogen-activated protein kinase (MAPK) signaling pathways might contribute to OA development [ 57 ]. Interestingly, our GO and KEGG analysis showed that several unreported processes such as muscle cell proliferation, cell-cell adhesion, and chemokine ligand 2 production and signaling pathways including Hippo signaling pathway, Wnt signaling pathway, and Ras signaling pathway were particularly identified in Tibetan OA patients compared to the Chinese Han OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA is a systematic biological algorithm [26], which is used to reveal the association between genes and clinical phenotypes [47]. It has been widely used to identified potential biomarkers for Alzheimer's disease [48], breast cancer [49], and osteoarthritis [50]. In this paper, WGCNA identified 7 modules.…”
Section: Discussionmentioning
confidence: 99%
“…Long Intergenic Non-Coding RNAs. Studies this year identified differentially expressed lncRNA in OA synovium [63], and long-intergenic non-coding RNA in hip OA cartilage [64].…”
Section: Long Non-coding Rnasmentioning
confidence: 99%